Substrate Compositional Variation with Tissue/Region and Gba1 Mutations in Mouse Models–Implications for Gaucher Disease - Sun, Ying; Zhang, Wujuan; Xu, You-Hai; Quinn, Brian; Dasgupta, Nupur; Liou, Benjamin; Setchell, Kenneth D. R.; Grabowski, Gregory A. (PloS one, 2013)
Gaucher disease results from GBA1 mutations that lead to defective acid β-glucosidase (GCase) mediated cleavage of glucosylceramide (GC) and glucosylsphingosine as well as heterogeneous manifestations in the viscera and CNS. The mutation, tissue, and age-dependent accumulations of different GC species were characterized in mice with Gba1 missense mutations alone or in combination with isolated saposin C deficiency (C*). Gba1 heteroallelism for D409V and null alleles (9V/null) led to GC excesses primarily in the visceral tissues with preferential accumulations of lung GC24∶0, but not in liver, spleen, or brain. Age-dependent increases of different GC species were observed. The combined saposin C deficiency (C*) with V394L homozygosity (4L;C*) showed major GC18:0 degradation defects in the brain, whereas the analogous mice with D409H homozygosity and C* (9H;C*) led to all GC species accumulating in visceral tissues. Glucosylsphingosine was poorly degraded in brain by V394L and D409H GCases and in visceral tissues by D409V GCase. The neonatal lethal N370S/N370S genotype had insignificant substrate accumulations in any tissue. These results demonstrate age, organ, and mutation-specific quantitative differences in GC species and glucosylsphingosine accumulations that can have influence in the tissue/regional expression of Gaucher disease phenotypes.